Adolescent Versus Adult Stalking: A Brief Review. Issue 4 (7th August 2016) - Roberts, Karl; Tolou-Shams, Marina; Madera, Kaila
ABSTRACT: This practice update considers adolescent stalking. Adolescent stalking is an area of research that deserves further study, given findings from the adult stalking literature that suggest significant public health and legal consequences associated with these behaviors. However, very little is known about this phenomenon, its potential differentiation from adolescent dating violence or bullying, and directions to take for future research. A comprehensive review across five scientific databases yielded a total of nine peer-reviewed manuscripts incorporating varying sample sizes and adolescent populations. A synthesis of existing research suggests that adolescent stalking exists at levels at least as high as that documented among adults but appears to have some notable differences (e.g., behavioral patterns, risk factors) from stalking behaviors among adults. To date, there exists no published representative population-based study of adolescent stalking behaviors and its health and legal consequences. Future research is needed to determine accurate prevalence statistics and to differentiate characteristics and public health impact of adolescent stalking from dating violence and bullying.